Insider Trading Laws and Stock Price Informativeness - Fernandes, Nuno (2013)
We investigate the relation between a country’s first-time enforcement of insider trading laws and stock price informativeness using data from 48 countries over 1980–2003. Enforcement of insider trading laws improves price informativeness, as measured by firm-specific stock return variation, but this increase is concentrated in developed markets. In emerging market countries, price informativeness changes insignificantly after the enforcement, as the important contribution of insiders in impounding information into stock prices largely disappears. The enforcement does not achieve the goal of improving price informativeness in countries with poor legal institutions. It does turn some private information into public information, thereby reducing the cost of equity in emerging markets.